Nonprofit organizations as interpretive communities: responses to policy reforms and the shaping of civil society in Ecuador. (2nd November 2019) - Appe, Susan
ABSTRACT: While they are often lumped together as one sector, nonprofit organizations represent diverse activities and objectives in the policy process. It is surprising that given this diversity, there are limited studies about the "multiple realities" that exist within a "nonprofit sector". This article examines the multiple realities found among nonprofit organizations. It explores how government creates regulatory policy targeting nonprofit organizations and how nonprofit organizations interpret and respond using the case of Ecuador in South America. The article asks: What do regulatory policies do and what target populations do they create? How do different nonprofit organizations interpret these policies? Given the answers to these questions, what are the political and social consequences for the development of civil society? Through an interpretive framework, the article contributes to the literature about how government creates target populations through policy, how policies act upon different nonprofits in different ways and how they interpret and respond to policy. The research considers what this might mean for organized civil society and development in general.